Stateczność Ruchu Pewnego Mechanizmu Płaskiego z Parami Postępowymi - Bogusz, W. (Engineering Transactions, 1959)
The problem discussed is that of critical velocity of elements in sliding junctions. The author discusses di plane mechanism with one sliding junction, and solves the problem of local disturbances of the motion by transversal vibration of the elastic element constituting the sliding junction with another element. The problem is reduced to the solution of a non-homogeneous equation of the Muthieu type. As a result, critical values for the period of sliding velocity are obtained.